Comparative Study on Treatment of Wastewater Using Natural and Artificial Coagulants - MOHAMAD JEFFERYDIN, SITI NUR NAJAH NAZIHAH; Rosli, Mohd Arif; Hashim, Nor Haslina (Progress in Engineering Application and Technology, 2022)
Blackwater and greywater are categorised as domestic wastewater, where blackwater has a higher concentration of pathogens than greywater[1]. The coagulation method is a wastewater treatment process that includes natural and artificial coagulants that help treat wastewater effectively. Consequently, bamboo charcoal is used as a natural coagulant in this study, while alum is used as an artificial coagulant. This study targets to identify the characteristic of bamboo charcoal, determine the potential of bamboo charcoal as a natural coagulant and compare the effectiveness between bamboo charcoal and alum in wastewater treatment towards pH, turbidity, COD, TSS, and DO according to Malaysia Water Quality Index. The wastewater was collected at UTHM Campus Pagoh Cafeteria. The characterisation of bamboo charcoal SEM, Fourier Transform Infrared Spectroscopy (FTIR) and Energy Dispersive X-ray (EDX) analysis. Next, the jar test was conducted with bamboo charcoal then continued with alum by varying the coagulant dosage (10mg/L, 20mg/L, 30mg/L, 40mg/L, and 50mg/L) and pH values (4, 6, 8, 10, and 12) to define the optimum dosage and pH. From the findings, the optimum dosage for bamboo charcoal and alum is at 30mg/L, and the optimum pH is 8. Recorded the performance of bamboo charcoal coagulant that removed 73.73% of turbidity, 48.73% of TSS, and 52.84% of COD. In contrast, alum removed 88.39% of turbidity, 61.82% of TSS, and 69.05% of COD. However, this study had achieved the objectives stated after-treatment of the wastewater with the natural and artificial coagulants, although below the permissible limit prescribed by the Environment Quality Act.